Pengaruh Lingkungan Keluarga Terhadap Kecerdasan Emosional Siswa Kelas VII SMP N 01 Rao Selatan - Erlandia Erlandia; Alfi Rahmi; Linda Yarni; Dodi Pasila Putra (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research was motivated by the existence of problems with several students at SMP N 01 Rao Selatan where there were several children who were unable to control their emotions, students who were not able to relate well to their friends, causing arguments that were not resolved well, and students who were less polite to their teachers and students. who lack responsibility for themselves, and students lack empathy for each other and teachers. This comes from a good family environment but the students' emotional intelligence is not good. The aim of this research is to see how much influence the family environment has on the emotional intelligence of class VII students at SMP N 01 Rao Selatan. The problem formulation in this research is how much influence the family environment has on the emotional intelligence of class VII students at SMP N 01 Rao Selatan. This type of research is quantitative correlational research which aims to determine the relationship between one variable and other variables. The population was all class VII students at SMP N 01 South Rao, and the research sample was 66 people. The sampling technique used is the simple random sampling method. Data collection in this research used a questionnaire. The data analysis technique uses product moment which requires the hypothesis to be accepted if the calculated r is greater than the r table and is assisted by the SPSS version 22 application. The results of the correlation analysis show that the calculated r value is 0.294. From this value, a determinant coefficient of 0.086 is obtained. So it can be concluded that the influence of the family environment on the emotional intelligence of class VII students at SMP N 01 Rao Selatan is 8.6%.